Mobile Health Interventions for Postpartum Maternal Health: An Umbrella Review - Fatimah Azzahroini Rajati; Faizah Betty Rahayuningsih (STIKep PPNI Jawa Barat, 2026)
Background: The postpartum period is a critical phase involving physical recovery, emotional adaptation, and social transition, which may affect maternal wellbeing. Limited access to continuous postnatal care can increase the risk of depression, inadequate self-care, and delayed recovery. Mobile health (mHealth) interventions have emerged as a potential solution to support continuity of care through remote monitoring, digital education, and ongoing support. Objective: This review aimed to synthesize evidence on the role of mobile health interventions in improving maternal health outcomes during the postpartum period. Methods: An umbrella review was conducted following the PRISMA 2020 framework. Relevant studies published between 2019 and 2025 were identified from PubMed, Scopus, CINAHL, and ScienceDirect. Eligibility was determined using the PICO framework, focusing on postpartum women receiving mHealth interventions compared to standard care. Five review-level studies were included and analyzed using descriptive and thematic synthesis. Results: mHealth interventions showed potential benefits in improving maternal self-efficacy, self-care engagement, physical activity, and overall wellbeing. They were also associated with reduced postpartum depression symptoms and improved adherence to follow-up care. Conclusion: Mobile health interventions may contribute positively to both psychological and physical health outcomes in postpartum women. However, the available evidence remains limited an indirect. Further high-quality primary studies are needed to establish effectiveness and inform clinical implementation.